2015
DOI: 10.1016/j.bbabio.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interaction studies revealed the bifunctional behavior of triheme cytochrome PpcA from Geobacter sulfurreducens toward the redox active analog of humic substances

Abstract: Humic substances (HS) constitute a significant fraction of natural organic matter in terrestrial and aquatic environments and can act as terminal electron acceptors in anaerobic microbial respiration. Geobacter sulfurreducens has a remarkable respiratory versatility and can utilize the HS analog anthraquinone-2,6-disulfonate (AQDS) as a terminal electron acceptor or its reduced form (AH2QDS) as an electron donor. Previous studies set the triheme cytochrome PpcA as a key component for HS respiration in G. sulfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…On the other hand, Voordeckers et al ( 2010 ) showed that the simultaneous deletion of genes coding for outer-membrane cytochromes OmcB, OmcS, OmcT, OmcE, and OmcZ yielded to a complete inhibition of AQDS reduction. Under the hypothesis that AQDS or humic substances are unable to access the periplasmic space of G. sulfurreducens , the interaction studies between AQDS and PpcA should be envisioned as working models (Dantas et al, 2014 , 2015a ). These models are even more relevant as no structural data are currently available for any of the outer membrane cytochromes mentioned above.…”
Section: Methodological Improvements To Assist the Solution Structuramentioning
confidence: 99%
“…On the other hand, Voordeckers et al ( 2010 ) showed that the simultaneous deletion of genes coding for outer-membrane cytochromes OmcB, OmcS, OmcT, OmcE, and OmcZ yielded to a complete inhibition of AQDS reduction. Under the hypothesis that AQDS or humic substances are unable to access the periplasmic space of G. sulfurreducens , the interaction studies between AQDS and PpcA should be envisioned as working models (Dantas et al, 2014 , 2015a ). These models are even more relevant as no structural data are currently available for any of the outer membrane cytochromes mentioned above.…”
Section: Methodological Improvements To Assist the Solution Structuramentioning
confidence: 99%
“…The structures are highly conserved suggesting that the interacting regions with putative redox partners can be mapped in experiments carried out with the protein in the reduced or oxidized state. This was indeed confirmed by NMR chemical shift perturbation studies between PpcA and the humic substance analog, which revealed that this molecule interacts in the same region with the cytochrome ( Dantas et al, 2014a , 2015 ).…”
Section: Resultsmentioning
confidence: 54%
“… Comparison of the most affected residues in the redox complexes established between PpcA from G. sulfurreducens and the elctron acceptors Fe-NTA (this work), Fe-citrate ( Ferreira et al, 2017 ) and AQ(H 2 )DS ( Dantas et al, 2014a , 2015 ). The residues highlighted in red and blue correspond to those that showed a decrease in the peak data height above 40% or a significant deviation in their chemical shift, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations